Simulation of a photosynthesis - Grabovskaja, Marina; Švitra, Donatas (Lietuvos matematikos rinkinys, 2004)
It is observed the differential equations system. The stable periodic solutions of the differential equations system of neutral type is constructed, which is based on the theory of bifurcations.